Web-based and blended educational tools and innovations - Karacapilidis, Nikos, editor; Raisinghani, Mahesh S., 1967-, editor; Ng, Eugenia M. W., 1959-, editor (Hershey P.A. : Information Science Reference)
"This book contributes to this search for better teaching methods by exploring the technical, social, cultural, organizational, human, cognitive, and commercial impact of technology in education"--Provided by publisher